Pengaruh Komunikasi Interpersonal Pedagang Madura Terhadap Akulturasi Budaya dan Etos Kerja Masyarakat Lokal di Pasar Larangan Sidoarjo - Didik Hariyanto; Lina Nur Azizah (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to know how is the effect of interpersonal communication Madurese traders to the cultural acculturation and work ethic of local communities at Pasar Larangan Sidoarjo. The method used in this study is quantitative. The data collection used are questioner presented to 97 respondents who was local communities and Madurese traders at Pasar Larangan Sidoarjo, with simple random sampling technique. The data analysis used is simple linear regression. The result of this study is variable of interpersonal communication has an effect to the cultural acculturation and work ethic. Cultural acculturation has been proved by there is tolerance, the same shoes in economic, the feeling of sympathize to the other culture, the marriage between Madurese and Javanese and an intense interaction among communities. Meanwhile work ethic has been proved by four aspects as follows, time responsibility, toughand never give up, the feeling of being independently and also easy to adaptable.